Faktor-Faktor Yang Mempengaruhi Konservatisme Akuntansi - Priatiningsih, Dian; Myas Sari, Fangela (JAKA (Jurnal Akuntansi, Keuangan, dan Auditing), 2023)
The purpose of this study was to determine the effect of company growth, profitability, investment opportunity set, leverage, and firm size on accounting conservatism in Go Public manufacturing companies. The sample in this study is a manufacturing company in the food and beverage sub-sector consumer goods industry and is listed on the Indonesia Stock Exchange (IDX) during the period 2015–2019. The number of samples were 14 companies taken by purposive sampling method. The analytical method of this study uses multiple regression with the SPSS 20 program which has previously passed the classical assumption test. The results of this study indicate that company growth has a negative and significant effect on accounting conservatism. Profitability has a positive and insignificant effect on accounting conservatism. The investment opportunity set has a positive and significant effect on accounting conservatism. Leverage has a positive and significant effect on accounting conservatism. Firm size has a positive and insignificant effect on accounting conservatism.